2022
DOI: 10.1021/acs.iecr.2c00673
|View full text |Cite
|
Sign up to set email alerts
|

A Rigorous Membrane Gas-Solvent Contactor Model for Flowsheet Simulation of the Carbon Capture Process

Abstract: A rate-based membrane gas-solvent contactor model was programmed in Aspen Custom Modeler (ACM) and interfaced with the Aspen Plus software suite to enable flowsheet simulations of carbon capture processes. After validation with different sets of laboratory and pilot plant data, the model's rigorous approach was examined against the commercial RadFrac model of Aspen Plus used for conventional absorption−stripping column simulations. Under identical processing conditions, both models predicted similar results fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…Analyzing the solvent composition reveals that the ratio between MDEA and PZ is a crucial design parameter for carbon adsorption efficiency and process energy demand. Sarodan et al [27] reported that the discrepancy between the two models for the liquid and gas temperature profiles was sufficient (approximately ten degrees Celsius) to affect the transfer. Because the composition and flow rate of the outflow streams were nearly identical to what the RadFrac model predicted, the crime did not occur in the membrane contactor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analyzing the solvent composition reveals that the ratio between MDEA and PZ is a crucial design parameter for carbon adsorption efficiency and process energy demand. Sarodan et al [27] reported that the discrepancy between the two models for the liquid and gas temperature profiles was sufficient (approximately ten degrees Celsius) to affect the transfer. Because the composition and flow rate of the outflow streams were nearly identical to what the RadFrac model predicted, the crime did not occur in the membrane contactor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mass and energy balances are evaluated for the gas and liquid side, and chemical equilibrium is solved for the liquid phase. This kind of modelling approach has been presented in several journal publications [10,12,13,18]. The following assumptions have been made during model development:…”
Section: Hollow Fiber Membrane Contactor: Model Formulationmentioning
confidence: 99%
“…The estimation of the equilibrium concentration for each chemical species is done according to the model proposed by Astarita et al [19] and already employed in similar studies [12,13,18]. This approach is based on the evaluation of the equilibrium reaction constants (i.e., K eq,i , where i represents a specific chemical reaction) and the resolution of the molar balance equations assuming that the concentration of �CO 3 -2 � is negligible and all the dissolved CO2 is absorbed via reaction (2.4).…”
Section: Hollow Fiber Membrane Contactor: Model Formulationmentioning
confidence: 99%
See 2 more Smart Citations